Seven Shades of Black Thoughts: COVID-19 and Its Psychological Consequences on Cancer Patients - Garutti, Mattia; Cortiula, Francesco; Puglisi, Fabio (Frontiers in Oncology, 2020)
An outbreak of novel coronavirus (COVID-19) that started in Wuhan, China at the end of December 2019 is now rapidly spreading all over the world. COVID-19 infection is plaguing people around the world, not only physically but also psychologically, and oncologic patients are particularly exposed to this emotional threat. Here we describe the psychological threats that, in our opinion, cancer patients have to live with in these days: logistic overload, loneliness, fear, oxymoronic thoughts, helplessness, frustration and emotional siege. Moreover, we discuss some ideas and suggestions to handle them. The hope is to depict a pragmatic workflow to transform patients’ psychological frailties into positive connections with their physicians and healthcare staff. Managing effectively all these challenges now will likely translate in improving the standards of care when this infective storm will be over. Paradoxically, COVID-19 outbreak could be an opportunity to learn how better managing cancer treatment.